G349(P) Positive change is possible: overcoming the barriers to addressing paediatric obesity in the general outpatient population. (May 2019) - McClean, A; O'Connor, B; Orr, K; Anderson, P; Burke, S; MacKenzie, D; Anandarajan, M
Abstract : Background: Childhood obesity negatively impacts physical health, mental wellbeing and shortens life expectancy 1 . A 2017 audit of children attending our district hospital's outpatient clinics (OPC) and rapid response unit (RRU) revealed: 13% of children were overweight and 15% were obese. 86% of overweight and obese children were not picked up by doctors or nurses. Staff focus groups and questionnaires indicated that many paediatric staff felt underprepared and apprehensive about addressing obesity with families. Aims: To increase childhood obesity recognition by ensuring that 50% of children will have Body Mass Index (BMI) calculated and plotted by May 2018. To increase staff knowledge, willingness and confidence to address childhood obesity with families. Methods: IHI QI methodology was used to introduce routine BMI plotting to RRU and OPC. A multidisciplinary team including dieticians, physiotherapists, psychologists, nurses and doctors was established. Plan-Do-Study-Act cycles introduced practical changes including I-pads with an app for quickly calculating BMI centiles. Parents provided essential feedback. Staff received multidisciplinary training utilising motivational interviewing techniques to have these crucial conversations with families. Staff feedback was collected through questionnaires, focus groups and semi-structured interviews. Results: BMI plotting was successfully introduced; going from a median of 0% to 100% for both OPC and RRU and increasing the recognition of overweight/obese children to 100%. 100% of staff who attended multidisciplinary training 'agreed'/'strongly agreed' that it improved their willingness, confidence and preparedness to address obesity with families. 100% of parents (27/27) who provided feedback were supportive of the project. 100% of parents stated that doctors have a duty to raise obesity with families. Conclusions: Routine BMI plotting has been successfully introduced to our outpatient department and spreading to other hospitals in Northern Ireland. We shared our innovative practice by hosting a regional paediatric obesity awareness day for all Northern Irish healthcare professionals. We are running a one-to-one health coaching pilot for families struggling with weight issues. We have applied for funding to expand this. Our vision is that all overweight/obese children are recognised and given support to achieve a healthier weight. References: Cabinet Office, Department of Health, HM Treasury, and Prime Minister's Office. Childhood obesity: a plan for action . https://www.gov.uk/government/publications/childhood-obesity-a-plan-for-action (accessed 17 October 2017).